Nuclear energy consumption and economic growth : evidence from states level in the United States - Tan, Chiang Ching (Universiti Malaysia Sarawak, 2011)
this study attempts to investigate the causal relationship between nuclear energy consumption and economic growth in 10 selected states of the United States (US) from the period of 1970 to 2008. test for units roots, cointegration, Granger causality and Variance Decomposition are presented. the main conclusion is that the causal relationship between nuclear consumption and economic growth is not uniform across states.